A DANCE PERFORMANCE ENTITLED “JAGO PABARATAN” AS A DRAMATIC VISUALIZATION OF THE STRUGGLE OF FIGHTING COCKS IN COCKFIGHTING - maharani, indira; Sasandjati, M.Hum, Dra. Jajuk Dwi (Solah, 2025)
The dance piece titled “Jago Pabaratan” is a dramatic dance work that highlights the phenomenon of cockfighting as a social reflection. Cockfighting, which is still widely practiced clandestinely in the northern part of Surabaya, serves as the backdrop for the creation of this dance piece. This dance piece visualizes the struggle of a rooster that is raised, trained, and ultimately fought for human interests in gambling practices. Through the exploration of representative and symbolic movements, the choreographer depicts the emotional conflict, suffering, and helplessness of the rooster in the cockfighting arena. The creation process of this dance piece employs Method I construction with a dramatic approach that emphasizes expression and the dynamics of atmosphere, without presenting a linear narrative. Artistic elements such as makeup, costumes, dance accompaniment, props, and setting are designed to strongly and expressively visualize the atmosphere of cockfighting. This dance piece is not only a medium for aesthetic expression but also a form of social criticism against the practice of cockfighting, which undermines human values and animal welfare.